EVALUATION OF LIVESTOCK MANAGEMENT PRACTICES AND THEIR RELATIONSHIP WITH PREDATORS IN CAMPECHE, MEXICO - Elías José Gordillo Chávez; Mircea Gabriel Hidalgo-Mihart; Juan Luis Peña-Mondragón; Víctor Javier Colino-Rabanal; Miguel Lizana-Avia (Tropical and subtropical agroecosystems, 2025)
Background: The management of negative interactions between livestock farming and predators is complex because of the multifactorial and dynamic nature of the underlying causes, which include human elements that complicate their management. Previous studies have shown that modifications in livestock management practices can significantly reduce these interactions. Therefore, it is crucial to identify the factors that promote these negative interactions to develop effective management strategies. Objective: To diagnose livestock management practices and their relationship with predators, exploring how these practices influence predation events and farmers' capacity to manage them. Methodology: Interviews and surveys were conducted with livestock farmers to gather information on their socioeconomic characteristics, livestock management practices, and perceived losses. The qualitative approach captured farmers' perceptions and their relationship with predators on their farms, Results: The results suggest that the interactions between livestock farming and predators are influenced by management practices that increase predation events and by farmers' limited capacity to manage them. The location of farms in fragmented landscapes exacerbates this situation, indicating the need to strengthen farmers' capacities. The meaning of the livestock and dependence of ranchers on diverse activities hinder the implementation of new livestock management practices. Implications: The study identifies possible key strategies, such as forage banks, electric fences, and vaccination programs, to reduce predation risks and improve livestock farming sustainability. These strategies should consider the economic and cultural contexts of ranching communities for effective implementation. Conclusion: Ranchers' management decisions are strongly shaped by cultural and traditional factors. Including ranchers in the codesigning of conservation strategies, together with education and capacity-building, is essential for align conservation efforts with their values and needs to ensure long-term success.